UAI: estudo de uma interjeição do português brasileiro - Hadinei Ribeiro Batista (2013)
This research takes as its object of study the item 'uai'. The purpose is to investigate two issues in relation to this item: a) to present a study about its grammatical and discursive status, and b) to discuss some hypotheses about its origin. For both, it is initially made one discussion about interjections and discourse markers. Then, it is developed one analysis of the variation between 'uai' and the forms 'ué/uê. About the origin, it is investigated the hypothesis of 'uai' has emerged from a diachronic evolution of the word 'olhai'. Beyond this, it is made a discussion of other hypothesis, independently of they have been attested in academic studies or not, about the possibility of the origin of 'uai' has occurred through borrowing language.